lncRNA PAN3-AS1 Modulates Cilium Assemble Signaling Pathway Through Regulation of RPGR as a Potential MS Diagnostic Biomarker: Integrated Systems Biology Investigation - Mostaghimi, Yasaman; Haddadi, Mohammad; Hojjati, Zohreh (Journal of molecular neuroscience, 2025)
Multiple sclerosis (MS), an autoimmune condition of the central nervous system (CNS), can lead to demyelination and axonal degeneration in the brain and spinal cord, which can cause progressive neurologic disability. MS symptoms include dysautonomia and progressive decline in motor abilities. In this investigation, we performed an integrated bioinformatics and experimental approach to find the expression level and interaction of a novel long non-coding RNA (lncRNA), PAN3-AS1 , in MS samples. Microarray analysis was performed by R Studio using GEOquery and limma packages. lncRNA-mRNA RNA interaction analysis was performed using the lncRRIsearch database. Pathway enrichment analysis was performed by KEGG and Reactome online software through the Enrichr database. Protein–protein interaction analysis was performed by STRING online software. Gene ontology (GO) analysis was performed by Enrichr database. Based on microarray analysis, lncRNA PAN3-AS1 has a significantly low expression in MS samples compared to the control (logFC − 1.2, adj. P . Val 0.03). qRT-PCR results approved bioinformatics analyses. ROC analysis revealed that PAN3-AS1 could be considered a potential diagnostic biomarker of MS. Based on lncRNA-mRNA interaction analysis, lncRNA PAN3-AS1 regulates the expression level of RPGR. RPGR and its protein interactome regulate the cilium assembly, chaperon-mediated autophagy, and microarray biogenesis. lncRNA PAN3-AS1 , as a significant low-expressed lncRNA in MS samples, could be a potential diagnostic MS biomarker. PAN3-AS1 might regulate the expression level of cilium assembly and chaperon-mediated autophagy. Dysregulation of PAN3-AS1 might affect the expression of RPGR and its protein interactome.